Brand Identity Design of the Bay Bali - Rizka Arika; Didit Widiatmoko Soewardikoen (Wimba : Jurnal Komunikasi Visual, 2014)
Bali is one of the famous tourist destinations all over the world. The tourists who come to Bali are increasing each year. This is followed by the increasing number of the resorts in all over the island. This issue make the competition between the resorts are getting tougher and also make every resort owner to compete to get the consumers. One of the resort on the island is The Bay which is now haven't has a brand identity or logo that could be used to communicate the brand, The Bay, to consumers. Methods used in the collection of data are survey, interview and literature studies. It was found from the data that The Bay needed to have a logo as the identity of The Bay as well as the guidance of logo usage. The results from surveys, interviews, and literature studies showed how customers choose their accommodation for holiday by choosing a comfortable resort. Survey and interview also differentiate the segment, which are upper middle class and foreigners. Balinese elements considered being included on the logo to add more traditional design of Bali on it. By the results of the data, the concept of The Bay logo is to adjust the traditional modern concept with the typical elements of Balinese culture and the image of The Bay. The logo is also visualized as in uniforms, transportation, hotel supplies, and stationery. This design is expected to help the Bay to communicate the brand to consumers.